To Redistribute or Not: A Politician's Dilemma - Fabiana Machado (Inter-American Development Bank (IDB), 2012)
A prerequisite for the adoption of redistributive policies in a democracy is that there be elected representatives who are either committed to or who have an incentive to advocate for such policies. To evaluate the prospects of such an outcome, this pa- per develops a theory exploring two fundamental factors at play during elections the critical political stage where citizens choose their representatives. The first is the lack of information about the policy inclinations of candidates. The second refers to two motivations compelling candidates into politics (and possibly at odds with each other): the opportunity to implement ones favored policies or to extract rents. Results indicate the existence of an equilibrium where high inequality and low redistribution can coexist. The theorys assumptions and outcomes are explored empirically using individual-level data collected in presidential election years in Brazil.
Keywords: C11; C70; D72; 330